Are HoLEP Surgical Videos on YouTube Biased and Misleading or Are They Leading the Industry? - Ömer Koraş; Fatih Gökalp; Ekrem Yıldırak; Hakan Sigva; Nezih Tamkaç; Sefa Porgali; Bilal Kulak; Ferhat Uçurmak; Sadık Görür (Journal of Urological Surgery, 2022)

(untitled)
Objective:In this study, we aimed to evaluate the content and quality of the most relevant YouTube videos related to holmium laser enucleation of the prostate (HoLEP) surgery.Materials and Methods:The keywords “HOLEP”, “laser enucleation” and “prostate enucleation” were used to perform a search on YouTube. Non-English language videos, videos with less than 4-minute duration, and repetitive videos were excluded. The reactions of the viewers to the videos were evaluated by recording the “total views”, “views/month” and “likes and dislikes” parameters. The data were divided into two groups based on the source of upload: Group 1 consisted of healthcare providers and group 2 comprised of commercial companies and for-profit organizations.Results:A total of 117 videos were included in the study. A significant portion of the videos (77.7%) had been uploaded by healthcare providers. There was no statistically significant difference between the uploading groups in terms of the DISCERN and the Global Quality score, scores (p=0.484 and p=0.108, respectively). However, Patient Education Materials Assessment Tool for Audiovisual Materials understandability and actionability scores were statistically significantly higher in group 2 (p=0.004 and p=0.022, respectively). In addition, when the misinformation scale was evaluated, there were significantly more videos with high-degree misinformation in group 2 (5.5% vs 33.3%, p=0.001).Conclusion:On video sharing platforms, such as YouTube, the number of reliable videos with accurate and appropriate guidance about diseases and treatments should be increased, and these videos should be allowed to be posted after they have been approved by relevant institutions, including healthcare associations and universities.